Wicked [compact disc, unabridged] : the life and times of the wicked witch of the West : a novel - Maguire, Gregory (Maguire, Gregory. Wicked years, 1997)
This re-creation of the land of Oz, tells the story of Elphaba, the Wicked Witch of the West, who wasn't so wicked after all. Past the yellow brick road and into a phantasmagoric world rich with imagination and allegory, Wicked just might change the reputation of one of the most sinister characters in literature.